Cationic Pd(II)/bipyridine-catalyzed conjugate addition of arylboronic acids to α, β-unsaturated carboxylic acids in aqueous media. Issue 13 (28th March 2018) - Ni, Yuxin; Song, Kaixuan; Shen, Kai; Yang, Zhenyu; Liu, Rui; Lin, Shaohui; Pan, Qinmin
Graphical abstract: Highlights: Highly efficient Pd(II)-catalyzed conjugate addition in pure water. Easily scaled up 1.0 g. Products easily purified by filtration without columns. Catalyst loading could be lowered to 1.0 mol% with modest yields. Reaction is air and moisture insensitive. 11 of 20 examples yielded >90% with high functional groups tolerance. Abstract: An in-situ generated cationic Pd(II)/bipyridine-catalyzed conjugate addition of arylboronic acids to α, β-unsaturated carboxylic acids in water was developed and optimized. For most substrates, nearly quantitative yields were given, and the products can be purified by simple washing without column chromatography. The reaction can be scaled up to 1.0 g easily with excellent yields. Also the loading of catalyst can be lowered to 1.0 mol% with modest yields, and the reaction provided a mild and easy way to synthesize β-disubstituted carboxylic acids.